Penegakan Hukum dalam Kasus Malapraktek: Penelitian - Rian Prayudi Saputra; Linda Susanti; Niken Ayu; Shindi Zahra; Silfina Agustin (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This study aims to examine criminal law enforcement in medical malpractice cases. Using library research methods, data was collected from various sources, such as books, journals, and magazines, to analyze and address the issues under study. The results indicate that a physician can be held criminally liable for malpractice if two main elements are met: an unlawful act (objective element) and fault on the part of the perpetrator, either intentional or negligent (subjective element). Furthermore, this article outlines several parameters for identifying suspected violations of the law, including due care (zorgvuldigheid), appropriate diagnosis and therapy, and compliance with professional standards and the principle of proportionality. This study concludes that physicians need to understand their legal responsibilities to anticipate potential lawsuits from patients.